A content analysis of exploring beauty ideals transformation, advertising values and product images in YouTube video advertisements of beauty and personal care brands - Wang, JW (2020)
Global beauty and personal care (BPC) markets have grown dramatically in the 21st century with the advance of business, technology, and globalisation. The use of models in advertising BPC products and sustaining unrealistic beauty standards is widespread in advertisements. However, beauty ideals portrayed in such advertisements can cause potential consumers to become dissatisfied with their physical appearance as well as encourage other health issues, such as eating disorders. Companies have been criticised for creating unrealistic standards of beauty. Therefore, some BPC brands have started to transform their definitions of beauty from these unrealistic ideals to positive body images or those of women’s empowerment in advertisements, especially on social media. The focus of this research is to investigate the transformation of beauty ideal by exploring the relationship between beauty types, referring to body images and beauty from both internal and external of people, and advertising values in YouTube video advertisements. Based on the “Match-up hypothesis”, the effects of endorsements in advertisements can vary and consumers are more likely to have favourable evaluations of products if beauty types and product images fit well with their pre-existing self-image. This dissertation will also evaluate how beauty types and advertising values match with BPC products by adopting a content analysis approach. This dissertation uses the value framework by Pollay (1983), the beauty type model from Solomon et al. (1992), and transformed beauty types by Cohen et al. (2019) and Windels et al. (2020) to categorise 66 YouTube advertisements from Covergirl, Dove, Hello Flo and Pantene from 2010 to 2020. The findings from this research provide evidence that most advertisements moving away from unrealistic beauty ideals instead promote positive body images, with Dove and Hello Flo challenging beauty ideals more frequently than Covergirl and Pantene. Matching beauty types and advertising values with product images have been found in most analysed YouTube advertisements. The main conclusions drawn from this study are that BPC brands have redefined beauty more so than beauty ideals themselves in the four brands’ YouTube advertisements. Moreover, the existence of interrelationships between certain beauty types and advertising values vary by brand due to different product images. Due to the global pandemic in 2020, consumers have moved towards shopping online instead of in brick-and-mortar stores, thus brands with a strong online presence can perform better than their offline counterparts. This dissertation recommends that although embracing the transformation of beauty ideals in digital advertisements can be an ethical business practice, advertisers should consider whether their product images match with transformed beauty types and use the interrelationship between transformed beauty types and advertising values.